Mesyl phosphoramidate oligonucleotides as potential splice-switching agents: impact of backbone structure on activity and intracellular localization - Hammond, SM; Sergeeva, OV; Melnikov, PA; Goli, L; Stoodley, J; Zatsepin, TS; Stetsenko, DA; Wood, MJA (Mary Ann Liebert, 2021)
A series of 2′-deoxy and novel 2′-O-methyl and 2′-O-(2-methoxyethyl) (2′-MOE) oligonucleotides with internucleotide methanesulfonyl (mesyl, μ) or 1-butanesulfonyl (busyl, β) phosphoramidate groups has been synthesized for evaluation as potential splice-switching oligonucleotides. Evaluation of their splice-switching activity in spinal muscular atrophy patient-derived fibroblasts revealed no significant difference in splice-switching efficacy between 2′-MOE mesyl oligonucleotide and the corresponding phosphorothioate (nusinersen). Yet, a survival study with model neonatal mice has shown the antisense 2′-MOE mesyl oligonucleotide to be inferior to nusinersen at the highest dose of 40 mg/kg. A reason for their lower activity in vivo as ascertained by cellular uptake study by fluorescent confocal microscopy in HEK293 cell line could possibly be ascribed to compromised endosomal release and/or nuclear uptake of the 2′-OMe or 2′-MOE μ- and β-oligonucleotides compared to their phosphorothioate analog.